3
$\begingroup$

Today Question

if $a>\dfrac{1}{4}$, show that $$\sum_{n=1}^{\infty}\dfrac{1}{n^2-n+a}=\dfrac{\pi}{\sqrt{4a-1}}\cdot\dfrac{e^{\pi\sqrt{4a-1}}-1}{e^{\pi\sqrt{4a-1}}+1}\tag{1}$$

I have konw that solution:

$$\sum_{n=1}^{\infty}\dfrac{1}{n^2+1}=\dfrac{\pi}{2}\dfrac{e^{2\pi}+1}{e^{2\pi}-1}-\dfrac{1}{2}$$

solution: note

$$e^{ax}=\dfrac{\pi^{2\pi a}-1}{\pi}\left(\dfrac{1}{2a}+\sum_{n=1}^{\infty}\dfrac{a\cos{nx}-n\sin{x}}{n^2+a^2}\right)$$ let $a=1,x=0$,then we have $$\sum_{n=1}^{\infty}\dfrac{1}{n^2+1}=\dfrac{\pi}{2}\dfrac{e^{2\pi}+1}{e^{2\pi}-1}-\dfrac{1}{2}$$

But for $(1)$ I have $$\sum_{n=1}^{\infty}\dfrac{1}{(n-\frac{1}{2})^2+a-\frac{1}{4}}$$ Then I can't ,Thank you for your help.

$\endgroup$
  • $\begingroup$ Just curious: does anyone know where the expression for $e^{ax}$ comes from? Is it a Fourier series? $\endgroup$ – angryavian Oct 30 '13 at 17:59
2
$\begingroup$

Complete the square in the summand to get

$$\sum_{n=1}^{\infty} \frac{1}{\left ( n-\frac12\right)^2+\left (a-\frac14\right)}$$

Note that the sum is symmetric and equal to

$$\frac12 \sum_{n=-\infty}^{\infty} \frac{1}{\left ( n-\frac12\right)^2+\left (a-\frac14\right)}$$

so that we may use the residue theorem to evaluate the sum. I will skip the steps involved in deriving the general result, but will just state it here:

$$\sum_{n=-\infty}^{\infty} f(n) = -\sum_{k} \operatorname*{Res}_{z=z_k} \pi \, \cot{(\pi z)} \, f(z)$$

where the $z_k$ are poles of $f$, which obeys certain integrability conditions. Details may be found elsewhere within this site.

In this case,

$$f(z) = \frac{1}{\left ( z-\frac12\right)^2+\left (a-\frac14\right)}$$

which has poles $z_{\pm} = \frac12 \pm i \sqrt{a-\frac14}$. The sum is therefore equal to

$$-\frac{\pi}{2} 2 \Re{\left [\frac{\cot{\pi \left ( \frac12 + i \sqrt{a-\frac14}\right )}}{i 2 \sqrt{a-\frac14}} \right ]} = \frac{\pi}{\sqrt{4 a-1}} \tanh{\left ( \pi \sqrt{4 a-1}\right)}$$

which matches the result to be shown.

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

First thing you can try is $$ \sum_{n=1}^{\infty} \frac{1}{n^2+4a-1}=\sum_{n=1}^{\infty} \frac{1}{(2n)^2+4a-1}+\sum_{n=1}^{\infty}\frac{1}{(2n-1)^2+4a-1} $$ You can find $$ \sum_{n=1}^{\infty} \frac{1}{n^2+4a-1}, $$ and $$ \sum_{n=1}^{\infty} \frac{1}{(2n)^2+4a-1}$$ using the identity.

By the way, the formula you wrote for Fourier series does not look right, maybe check for typos.

The right formula that you should obtain is $$ \sum_{n=1}^{\infty} \frac{1}{n^2+a^2}=\frac{1}{2a}\left(\pi\frac{e^{2\pi a}+1}{e^{2\pi a}-1}-\frac{1}{a}\right) $$ The first sum is: $$ \frac{1}{2\sqrt{4a-1}}\left(\pi\frac{e^{2\pi \sqrt{4a-1}}+1}{e^{2\pi \sqrt{4a-1}}-1}-\frac{1}{\sqrt{4a-1}}\right) $$ The second sum is: $$ \frac{1}{4}\frac{1}{\sqrt{4a-1}}\left(\pi\frac{e^{\pi \sqrt{4a-1}}+1}{e^{\pi \sqrt{4a-1}}-1}-\frac{2}{\sqrt{4a-1}}\right) $$ Hence, the final result is: $$ \sum_{n=1}^{\infty}\frac{1}{(2n-1)^2+4a-1}=\frac{1}{4}\frac{1}{\sqrt{4a-1}}\left(\pi\frac{e^{\pi \sqrt{4a-1}}-1}{e^{\pi \sqrt{4a-1}}+1}\right). $$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.